Spreading of phonological activation in dyslexia throughout life - Buil-Legaz, Lucía; Rodríguez-Ferreiro, Javier; Cuetos, Fernando; Suárez-Coalla, Paz (Revista de Investigación en Logopedia, 2023)
We studied the developmental course of the spreading of phonological activation in individuals with and without dyslexia by means of a phonological version of the Deese/Roediger-McDermott false memory task. The false memory effect is assumed to reflect the spreading of activation from the presented stimuli to similar words in the lexicon. We assessed 35 volunteers with dyslexia and a group of matched controls with ages ranging from 6 to 58 years. They were first presented with six lists of ten two-syllable words each, all of which shared one syllable with a reference unpresented word. Then, they answered a recognition questionnaire including 24 presented words, 18 phonologically related unpresented words, and 12 unrelated unpresented words. False recognition of phonologically related words increased with age in the control group but stayed at very low levels in the dyslexia group. Our study indicates the existence of a deficit in the spreading of phonological activation in individuals with dyslexia throughout life.